Successes and lessons learned from a mobile health behavior intervention to reduce pain and improve health in older adults with obesity and chronic pain: a qualitative study - Brooks, Amber K.; Athawale, Abha; Rush, Virginia; Yearout, Abigail; Ford, Sherri; Rejeski, W. Jack; Strahley, Ashley; Fanning, Jason (Frontiers in Pain Research, 2024)
Introduction: Chronic pain is a prevalent issue among older adults in the United States that impairs quality of life. Physical activity has emerged as a cost-effective and nonpharmacological treatment for chronic pain, offering benefits such as improved physical functioning, weight loss, and enhanced mood. However, promoting physical activity in older individuals with chronic pain is challenging, given the cyclical relationship between pain and sedentary behavior. The Mobile Intervention to Reduce Pain and Improve Health (MORPH) trial was designed as an innovative, mobile health (mHealth) supported intervention to address this issue by targeting daylong movement, weight loss, and mindfulness to manage pain in older adults with chronic multisite pain. The objective of this paper is to provide the result of a qualitative analysis conducted on post-intervention interviews with MORPH participants.Methods: At the conclusion of the MORPH study, 14 participants were interviewed regarding their experience with the program. All interviews were conducted by phone before being transcribed and verified. A codebook of significant takeaways was created based on these accounts. Summaries were further synthesized into themes using the principles of thematic analysis.: Three key themes of the MORPH intervention emerged from the qualitative interviews: MORPH technology (smart scales, Fitbit, MORPH Companion App) facilitated program adherence and accountability; MORPH intervention components (food tracking and mindfulness activities) facilitated program adherence and awareness, respectively; and, group meetings provided motivational support and accountability. Mobile health technologies, including a dedicated MORPH app, facilitated self-monitoring strategies, helped to break the cycle of old habits, and provided participants with immediate feedback on successes; however, technical issues required timely support to maintain engagement. Food tracking contributed to adherence and accountability for weight loss. Mindfulness activities increased participants' awareness of anxiety provoking thoughts and pain triggers. Finally, social support via group meetings and connection, played a crucial role in behavior change, but participants noted consistency in the delivery medium was essential to fostering genuine connections.